Managing the Cloud Continuum: Lessons Learnt from a Real Fog-to-Cloud Deployment - Xavi Masip-Bruin; Eva Marín-Tordera; Sergi Sánchez-López; Jordi Garcia; Admela Jukan; Ana Juan Ferrer; Anna Queralt; Antonio Salis; Andrea Bartoli; Matija Cankar; Cristovao Cordeiro; Jens Jensen; et al. (Sensors, 2021)
The wide adoption of the recently coined fog and edge computing paradigms alongside conventional cloud computing creates a novel scenario, known as the cloud continuum, where services may benefit from the overall set of resources to optimize their execution. To operate successfully, such a cloud continuum scenario demands for novel management strategies, enabling a coordinated and efficient management of the entire set of resources, from the edge up to the cloud, designed in particular to address key edge characteristics, such as mobility, heterogeneity and volatility. The design of such a management framework poses many research challenges and has already promoted many initiatives worldwide at different levels. In this paper we present the results of one of these experiences driven by an EU H2020 project, focusing on the lessons learnt from a real deployment of the proposed management solution in three different industrial scenarios. We think that such a description may help understand the benefits brought in by a holistic cloud continuum management and also may help other initiatives in their design and development processes.